Spatial Distribution and Encounter Rates of Delphinids and Deep Diving Cetaceans in the Eastern Mediterranean Sea of Turkey and the Extent of Overlap With Areas of Dense Marine Traffic - Awbery, Tim; Akkaya, Aylin; Lyne, Patrick; Rudd, Laura; Hoogenstrijd, Gemma; Nedelcu, Madeleine; Kniha, David; Erdoğan, Mehmet Akif; Persad, Cherisse; Amaha Öztürk, Ayaka; Öztürk, Bayram (Frontiers in Marine Science, 2022)
Marine traffic has been identified as a serious threat to Mediterranean cetaceans with few mitigation strategies in place. With only limited research effort within the Eastern Basin, neither baseline species knowledge nor the magnitude of threats have been comprehensively assessed. Delineating the extent of overlap between marine traffic and cetaceans provides decision makers with important information to facilitate management. The current study employed the first seasonal boat surveys within the Eastern Mediterranean Sea of Turkey, incorporating visual and acoustic survey techniques between 2018 and 2020 to understand the spatial distribution of cetacean species. Additionally, marine traffic density data were retrieved to assess the overlap with marine traffic. Encounter rates of cetaceans and marine traffic density were recorded for each 100 km2 cell within a grid. Subsequently, encounter and marine traffic density data were used to create a potential risk index to establish where the potential for marine traffic and cetacean overlap was high. Overall, eight surveys were undertaken with a survey coverage of 21,899 km2 between the Rhodes and Antalya Basins. Deep diving cetaceans (sperm and beaked whales) were detected on 28 occasions, with 166 encounters of delphinids of which bottlenose, striped and common dolphins were visually confirmed. Spatially, delphinids were distributed throughout the survey area but encounter rates for both deep diving cetaceans and delphinids were highest between the Rhodes and Finike Basins. While sperm whales were generally detected around the 1000m contour, delphinids were encountered at varying depths. Overall, two years of monthly marine traffic density were retrieved with an average density of 0.37 hours of monthly vessel activity per square kilometer during the study period. The mean density of vessels was 0.32 and 1.03 hours of monthly vessel activity per square kilometer in non-coastal and coastal waters respectively. The Eastern Mediterranean Sea has several important shipping lanes within the study area. Two priority areas for deep diving cetacean and a large priority area for cetaceans were identified in the waters between Marmaris and Finike where high cetacean encounters and dense marine traffic overlapped. The current study revealed important habitats for cetaceans within the data deficient Eastern Mediterranean Sea and delineated potential risk area where marine traffic should be limited.